Shift Share Analysis Shift Share analysis Indonesia masa pandemi Covid-19 - Lucky Rachmawati; Hendry Cahyono; Jaka Nugraha; Ladi Watjuba; Nurul Hanifa (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2020)
The Corona Virus pandemic threatens the fabric of people's lives in all fields, including in the economic field. This study aims to analyze the shift in the economic sector during the Corona Virus pandemic. This research is a descriptive type of research with a mathematical quantitative approach using the Shift Share analysis tool to analyze sectoral shifts due to the outbreak of the Corona Virus Pandemic. Specifically related to the elements of the shift share analysis, it is found that: overall, all sectors in the five provinces, the value of the effect of national growth is negative; the value of the industrial mix, in the five provinces of Indonesia has the same sectoral characteristics. The industrial mix has a positive value in some sectors and the industrial mix is negative in other sectors; the value of Regional Shares in the five provinces varies considerably. This of course is influenced by the ability of each province to produce; the characteristics of the total effect value vary in each sector in each province. The total effect value is positive, this means that a sector in a province is classified as progressive. The total effect value is negative, this means that a sector in a province is classified as conservative. Suggestions for future researchers are that this research does not include elements of economic agglomeration. If there are researchers who are interested in further research, maybe it can be added related to the elements of economic agglomeration.